2006
DOI: 10.1016/j.jembe.2006.05.016
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the SW Atlantic burrowing crab Chasmagnathus granulatus on the intertidal razor clam Tagelus plebeius

Abstract: The deposit feeding burrowing crab Chasmagnathus granulatus and the suspension feeding burrowing clam Tagelus plebeius occur sympatrically in the intertidal flats of the south western Atlantic estuarine environments. Common ecological theory predicts negative effects of deposit feeder bioturbation on co-occurring suspension feeders up to complete exclusion of the latter. By means of descriptive and experimental approaches performed at the Mar Chiquita coastal lagoon (37°32′S-57°19′W; Argentina) we show that wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…LOMOVASKI et al (2006) found negative allometry for the height/length (H/SL) and width/length (W/SL) relationships of T. plebeius. GASPAR et al (2002) reported discrepancies in the allometric relationships of Pharus legumen Linnaeus, 1758 (Bivalvia, Solecurtidae),which, in spite of being considered a great burrower, displays negative allometry for H/SL and is isometric for W/SL.…”
Section: Resultsmentioning
confidence: 94%
“…LOMOVASKI et al (2006) found negative allometry for the height/length (H/SL) and width/length (W/SL) relationships of T. plebeius. GASPAR et al (2002) reported discrepancies in the allometric relationships of Pharus legumen Linnaeus, 1758 (Bivalvia, Solecurtidae),which, in spite of being considered a great burrower, displays negative allometry for H/SL and is isometric for W/SL.…”
Section: Resultsmentioning
confidence: 94%
“…The density of C. japonica, a filter feeder, was significantly higher when M. japonicus was excluded. Previous studies performed on soft-bottom communities have shown that bioturbators inhibited feeding and subsequent growth of suspension feeders owing to sediment disturbance (Rhoads & Young 1970, Lomovasky et al 2006. Bioturbation by M. japonicus might also suppress the activities of C. japonica in this flat and significantly affect their survival.…”
Section: Effects Of M Japonicus On Macro-infauna Densitymentioning
confidence: 94%
“…Cage exclusion experiments are the most common method used to investigate how particular species affect the benthic community (e.g. Reise 1978, Posey et al 1991, Botto & Iribarne 1999, Webb & Eyre 2004, Lomovasky et al 2006. In the present study, crab exclusion experiments were conducted to clarify the effects of M. japonicus on the abundance of macro-infauna and on the sedimentary environments in the intertidal mud flat of the Tama river estuary, Tokyo Bay.…”
Section: Introductionmentioning
confidence: 99%
“…However, these taxa exhibit different strategies of growth and space colonization: while sponges and bryozoans are colonial species that occupy space by lateral growth, barnacles and bivalves mainly depend on gregarious recruitment for space occupation (Jackson 1977;Sebens 1982Sebens , 1986. In soft-bottom habitats, trophic-based studies may overlook key functions, such as nutrient cycling, that are often biologically driven (the bioturbatory activities of benthic species affect sediment geochemistry, see Reise 1985;Levinton 1995;Heip et al 2001;Lohrer et al 2005) and habitat provision (habitat engineering and bio-construction, see Jones et al 1994;Meysman et al 2002;Reise 2002;Lomovasky et al 2006). In this context, knowledge of multiple aspects of ecosystem function can be attained by considering as many functionally important traits as possible (Norling et al 2007).…”
Section: Introductionmentioning
confidence: 99%